Self-Compassion as a Way to Embrace Loneliness in University Students - Dicky Sugianto; Handayani Sutanto; Christiany Suwartono (PSIKODIMENSIA, 2020)
This study aims to examine the relationship between self-compassion and loneliness in university students. Three hundred and twenty-nine registered university students in Jabodetabek that were recruited through purposive sampling participated in the study. Self-compassion was measured using Skala Welas Diri and loneliness was measured using UCLA Loneliness Scale version 3. Data was analyzed using linear regression and Pearson correlation to observe the relationship between components of self-compassion and loneliness. Results shows that self-compassion significantly predicts loneliness in students and self-compassion components are related to loneliness. The results suggest that self-compassion training may benefit the students to alleviate their loneliness.